Trans-arterial omental flap protection for infected femoral artery aneurysm in a patient with Parkes-Weber syndrome - Natsumi Iijima, MD; Ryosuke Taniguchi, MD, PhD; Masaru Kimura, MD, PhD; Takuro Shirasu, MD, PhD; Toshio Takayama, MD, PhD; Katsuyuki Hoshina, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
We report a case of a 75-year-old man diagnosed with Parkes-Weber syndrome with an infected common femoral artery aneurysm secondary to chronic venous ulcers and groin infection. Given the symptomatic and rapid enlargement of the aneurysm, emergency aneurysmectomy and crossover femoro-femoral bypass were performed with an omental flap routed intraluminally through the aneurysm of the ipsilateral external iliac artery. The transarterial route enabled the short-cutting of the omental flap and the potential prevention of infection in the adjacent external iliac artery. The patient’s condition was uneventful 9 months postoperatively.